How you provide corrective feedback makes a difference: The motivating role of communicating in an autonomy-supporting way - Mouratidis, A.; Lens, W.; Vansteenkiste, M. (Journal of Sport & Exercise Psychology, 2010)
We relied on self-determination theory (SDT; Deci & Ryan, 2000) to investigate to what extent autonomy-supporting corrective feedback (i.e., feedback that coaches communicate to their athletes after poor performance or mistakes) is associated with athletes` optimal motivation and well-being. To test this hypothesis, we conducted a cross-sectional study with 337 (67.1% males) Greek adolescent athletes (age M = 15.59, SD = 2.37) from various sports. Aligned with SDT, we found through path analysis that an autonomy-supporting versus controlling communication style was positively related to future intentions to persist and well-being and negatively related to ill-being. These relations were partially mediated by the perceived legitimacy of the corrective feedback (i.e., the degree of acceptance of corrective feedback), and, in turn, by intrinsic motivation, identified regulation, and external regulation for doing sports. Results indicate that autonomy-supporting feedback can be still motivating even in cases in which such feedback conveys messages of still too low competence.